2018
DOI: 10.21608/ejchem.2018.4069.1359
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of wet-chemistry Cu co-doped ZnTiO3 thin films deposited by spin coating method

Abstract: Z n 1-x TiO 3 :xCu (x=0%, 1%, 5%) thin films were prepared on glass and quartz substrates via the sol-gel method (wet-chemistry) and spin coating process. Structural and optical properties of the prepared films have been characterized by X-ray diffraction, field emission scanning electron microscope and UV-visible spectrophotometer. The doping of the thin films by different concentration of Cu ions exhibited change in structure from cubic to hexagonal system. The average crystalline size was calculated from X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Both pure nano-CaO-chitosan and loaded with nano-CaO-0.4 Ag-chitosan are chosen as the two representative samples to study the morphological characteristics by TEM and Fe-SEM, as manifested in Fig. (3). The main evidence of the internal structure of nano-CaO and nano-CaO-0.4 Ag into chitosan polymer matrix are confirmed with TEM images Fig.…”
Section: 3tem/semmentioning
confidence: 84%
See 1 more Smart Citation
“…Both pure nano-CaO-chitosan and loaded with nano-CaO-0.4 Ag-chitosan are chosen as the two representative samples to study the morphological characteristics by TEM and Fe-SEM, as manifested in Fig. (3). The main evidence of the internal structure of nano-CaO and nano-CaO-0.4 Ag into chitosan polymer matrix are confirmed with TEM images Fig.…”
Section: 3tem/semmentioning
confidence: 84%
“…Metal oxide (MO) nanoparticles have recently gotten a lot of interest because of their potential applications in optoelectronics, catalysts, adsorbents, and bactericides [1][2][3]. Because of their plentiful supply of raw materials, good thermal stability, low biological toxicity, and bio-degradability, MO nanoparticles have a wide range of applications [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The peaks positioned at around 350 and 235 cm −1 are ascribed to the vibration-modes of v 2 (LO, TO), and v 4 (LO), respectively, which are the characteristic peaks of hexagonal ZnTiO 3 (Ahn et al 2005). Regarding the strong Raman, the peak appeared at around 723 cm −1 , mainly is attributed to A 1g mode of cubic Zn 2 TiO 4 (Hou et al 2005;El Nahrawy et al 2018).…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…CaO nanoparticles were prepared by solgel method using Ca(NO3)2.H2O as Ca precursor. So, controlled sol-gel manufacture of Ca oxide nanoparticles is in uential for highly effective applications [9,10]. It is reported that the sol-gel solution method provides a high degree of control through the fabrications yields [11,12].…”
Section: Introductionmentioning
confidence: 99%